As restaurações em lesões cervicais não cariosas pela “técnica sanduíche” apresentam taxas de retenção superiores à técnica restauradora com resina composta? uma revisão sistemática e meta-análise - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
Objectives: This systematic review and meta-analysis compared the retention rates of non-carious cervical restorations (NCCLs) restored with the sandwich technique (a lining of glass ionomer cement [GIC] or resin-modified glass ionomer cement [RMGIC] + composite resin [CR]) or CR restorations. Secondary outcomes such as marginal discoloration, marginal adaptation, color match and secondary caries were also analyzed. Methods: This study included randomized clinical trials (RCTs) that compared the retention rates of NCCLs restored with the “sandwich technique” with CR restorations. The search was performed in Cochrane Library, PubMed, Scopus and Web of Science among other databases. Grey literature was inspected as well as the abstracts from the IADR (1990-2017), ongoing and unpublished. The quality of the studies was evaluated using the Cochrane Collaboration bias risk tool. Data of primary and secondary outcomes were meta-analyzed at different follow-ups (one; two and three-year) using the random effects model. The quality of the body of evidence was assessed using the GRADE approach Results: Initially, a total of 3.645 articles were selected. After selection by titles, abstracts and full texts, 6 articles were found, but three were follow-ups of the same RCT and therefore a total of four studies remained for analysis. All studies were at unclear risk of bias. From all outcomes, only loss of retention was lower for the “sandwich technique” at the three-year follow-up (RR = 7.5; 95% CI 2.1 to 27.2; p = 0.002). Conclusions: Higher retention rates in NCCLs restorations were observed with the sandwich technique compared to CR restorations after three years of evaluation. Marginal discoloration, color match, marginal adaptation and secondary caries were not influenced by the restorative technique. Except from retention rates, graded as moderate, the quality of the evidence of the other outcomes was graded as low.
The restorations in non-carious cervical lesions by the "sandwich technique" have superior retention rates when compared to the restorative technique with composite resin? a systematic review and meta-analysis
Keywords: Cimentos de ionômeros de vidro; Restauração dentária permanente; Materiais dentários; Materiais dentários; Glass ionomer cements; Dental restoration permanent; Meta-analysis; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA